The Effectiveness of Digital-Based Snake and Ladder Learning Media in Improving Elementary School Students' Beginning Writing Skills - Hardiansyah, Framz; Subaydi; Maulidi, Rofiqi Nur; Nasrullah, Ahmad Syafiq; Hidayat, Ahmad Riyan (Global Action and Education for Society, 2026)
This study aims to assess the effectiveness of using digital-based snakes and ladders learning media in improving the basic writing skills of grade I students at SDN JULUK II. Writing is a fundamental skill that is critical to a child's academic progress, but often faces challenges, especially at the early grade level. The snakes and ladders game is one of the traditional games that is very popular with children and can be modified into learning media. Through digital adaptation, this game can be adapted to learning materials, including writing skills. Digital-based snakes and ladders media enables a learning experience that involves active interaction. Learners can learn to write while playing, which indirectly improves their motivation and writing skills. The method applied in this study was a quantitative approach with a quasi-experiment design of non-equivalent control group design, involving two groups: an experimental group that utilized digital media and a control group that applied conventional methods. The study showed a significant improvement in learners' writing skills, with 80.95% of learners achieving minimum completion after the treatment, compared to only 23.81% in the pretest. Research using simple linear regression indicated that the utilization of digital-based snakes and ladders learning media contributed positively to the improvement of writing skills. In conclusion, this media proved to be effective and can be recommended as an innovative learning tool to improve learners' beginning writing skills in primary schools